2014
DOI: 10.4161/cam.27841
|View full text |Cite
|
Sign up to set email alerts
|

p53 in cell invasion, podosomes, and invadopodia

Abstract: Cell invasion of the extracellular matrix is prerequisite to cross tissue migration of tumor cells in cancer metastasis, and vascular smooth muscle cells in atherosclerosis. The tumor suppressor p53, better known for its roles in the regulation of cell cycle and apoptosis, has ignited much interest in its function as a suppressor of cell migration and invasion. How p53 and its gain-of-function mutants regulate cell invasion remains a puzzle and a challenge for future studies. In recent years, podosomes and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 133 publications
1
19
0
Order By: Relevance
“…17 It has been observed for long time that the deletion of p53 allows fibroblast to migrate faster in wound healing assays, potentially due to the altered cell morphology and polarity. 14,21 This observation is not only limited to fibroblast, but also expanded to multiple cancer epithelial cell lines. 14,21 However, the underlying molecular mechanism of this regulation is, at least partially, kept unknown and requires delineated studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 It has been observed for long time that the deletion of p53 allows fibroblast to migrate faster in wound healing assays, potentially due to the altered cell morphology and polarity. 14,21 This observation is not only limited to fibroblast, but also expanded to multiple cancer epithelial cell lines. 14,21 However, the underlying molecular mechanism of this regulation is, at least partially, kept unknown and requires delineated studies.…”
Section: Introductionmentioning
confidence: 99%
“…14,21 This observation is not only limited to fibroblast, but also expanded to multiple cancer epithelial cell lines. 14,21 However, the underlying molecular mechanism of this regulation is, at least partially, kept unknown and requires delineated studies. It was discovered that the loss of p53 activates Rho signaling pathway, a well-established pathway to influence the way in which tumor cells migrate, to promote cell migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant p53 proteins (mutp53) lose wild-type p53 (wtp53) transcriptional activity and gain novel oncogenic functions that are independent of wtp53 (7). Accumulating evidence has recently revealed that mutp53 can promote invasion and motility through its activation of transforming growth factor  (TGF-), epidermal growth factor receptor (EGFR) and MET (8).…”
Section: Introductionmentioning
confidence: 99%
“…10 The number of cell types described to be able to form invadosomes is constantly increasing. Depending on the cell-specific functions and the extracellular context studied, invadosomes' molecular composition and the associated signaling pathways can differ.…”
mentioning
confidence: 99%